Wear-resistant plastic composition for plastic stools and preparation method of wear-resistant plastic composition
By foaming carbon nanotubes and TPU particles and blending titanium dioxide-loaded fibers with PP, the problems of insufficient wear resistance and photooxidation resistance of plastic stools during outdoor use are solved, and the long life and stability of plastic stools in outdoor environments are achieved.
Patent Information
- Application Number
- CN202510733082.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-04
- Publication Date
- 2025-10-03
AI Technical Summary
Plastic stools are susceptible to ultraviolet radiation and wind and sand erosion when used outdoors, resulting in insufficient wear resistance and resistance to photooxidation, which affects their service life.
By compounding carbon nanotubes with TPU particles and then foaming them, loading titanium dioxide on the surface of natural fibers and melt-blending them with PP to form a wear-resistant plastic composition, the wear resistance and anti-photooxidation properties of the plastic stool are improved.
The wear resistance and light oxidation resistance of the plastic stool are improved, and the service life is extended. In particular, it shows good stability in outdoor strong light and windy sand environments.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer compound compositions, and particularly relates to a wear-resistant plastic composition for plastic stools and a preparation method thereof. Background Art
[0002] Plastic is a high molecular polymer. Commonly used plastic materials include polypropylene (PP), polyethylene (PE), polycarbonate (PC), polyvinyl chloride (PVC) and ABS plastic. These materials have their own characteristics. PP material is strong and durable, with good heat resistance; PE material is light and portable, with strong water resistance; PC material has high transparency and strong impact resistance. Since plastic stools are used very frequently, they need to have excellent wear resistance to improve the service life and durability of plastic stools.
[0003] Plastic stools are also widely used outdoors. In outdoor environments, the ultraviolet rays in the sun will break the chemical bonds of plastic polymers, causing the plastic to crack and age, reducing the service life of the plastic stools. In outdoor usage scenarios, the use environment of beach chairs is the most harsh. Not only are there strong ultraviolet rays, but also accompanied by wind and sand wear and water vapor erosion, causing the plastic to photo-oxidize and crack, greatly reducing the service life of the plastic stools.
[0004] Patent CN112143138A discloses a type of recycled plastic particles and a method for preparing the same. By preparing an anti-aging agent, when exposed to light, the amino groups on the anti-aging agent molecules are converted into nitroxide free radicals that can exist stably for a long time. The nitroxide free radicals can effectively capture and inactivate the free radicals generated by the polymer, preventing photoaging and improving the light aging resistance of the plastic particles. However, in an environment with high water vapor content and wind and sand erosion, the wear resistance and water resistance of the plastic particles are poor. Simply improving the light aging resistance of the plastic particles cannot increase the service life of the plastic particles. Summary of the Invention
[0005] The purpose of the present invention is to solve the problem of how to improve the light oxidation resistance and wear resistance of plastics, and to provide a wear-resistant plastic composition for plastic stools and a preparation method thereof.
[0006] The present invention obtains foamed TPU particles by compounding carbon nanotubes and TPU particles and then foaming them to improve the wear resistance. Titanium dioxide is then evenly loaded on the surface of natural fibers, melt-blended with PP under the action of a compatibilizer, and finally blended with the foamed TPU particles to obtain a wear-resistant plastic composition that is resistant to ultraviolet light oxidation, thereby improving the service life of the plastic stool.
[0007] The purpose of the present invention can be achieved through the following technical solutions: A wear-resistant plastic composition for a plastic stool, comprising the following components in parts by mass: 90-100 parts of PP particles, 10-15 parts of titanium dioxide loaded fibers, 6-9 parts of polypropylene-g-maleic anhydride, 1-2 parts of zinc stearate, 30-40 parts of foamed TPU particles and 1-2 parts of silicone oil defoaming agent.
[0008] Furthermore, the titanium dioxide-loaded fiber is prepared by the following steps: The modified fiber is immersed in an ammonium fluorotitanate solution in a reactor and stirred for 10-12 hours. The precipitate is collected after filtration. The precipitate is immersed in a boric acid solution again and stirred for 3-5 hours. The precipitate is collected by filtration and vacuum dried to obtain titanium dioxide loaded fiber.
[0009] Furthermore, the usage ratio of the modified fiber, the ammonium fluorotitanate solution and the boric acid solution is 10-15 g: 100-150 mL: 150-200 mL; the concentration of the ammonium fluorotitanate solution is 0.1 M, and the concentration of the boric acid solution is 0.3 M.
[0010] Furthermore, the modified fiber is prepared by the following steps: After o-methoxyphenol is melted in a reactor, natural fibers crushed through a 40-mesh sieve are added thereto. Concentrated sulfuric acid is added to the reactor, the temperature is raised to 160-180° C., and the mixture is stirred and reacted for 60-80 minutes. After cooling, acetone is added thereto, and after stirring and dissolving, a 2M sulfuric acid solution is slowly added thereto. The precipitate is separated by filtration, washed, and vacuum dried to obtain the modified fiber.
[0011] Furthermore, the dosage ratio of o-methoxyphenol, natural fiber, concentrated sulfuric acid, acetone and sulfuric acid solution is 20-30 g: 10-15 g: 5-7 mL: 200-250 mL: 1.5-1.8 L.
[0012] Furthermore, the natural fiber is one of hemp fiber, jute fiber, ramie fiber, kenaf and sisal fiber.
[0013] Furthermore, the foamed TPU particles are prepared by the following steps: The composite TPU particles are placed in an autoclave, and after carbon dioxide is introduced to remove air, carbon dioxide is introduced at a pressure of 15-16 MPa and 90-100° C. for 20-40 minutes to saturate the autoclave. The pressure is then released to foam the composite TPU particles to obtain foamed TPU particles.
[0014] Furthermore, the composite TPU particles are prepared by the following steps: In a reaction kettle, TPU particles and N,N-dimethylformamide are magnetically stirred at 60-70° C. for 1.5-2 hours, carbon nanotube dispersion is added to the reaction kettle, the temperature is raised to 60-70° C., ultrasonic treatment is performed for 1-1.5 hours, and then the solvent is removed by rotary evaporation. The precipitate is vacuum dried to obtain composite TPU particles.
[0015] Furthermore, the usage ratio of TPU particles, N,N-dimethylformamide and carbon nanotube dispersion is 10-15 g: 100-150 mL: 100-150 mL.
[0016] Furthermore, the carbon nanotube dispersion is prepared by ultrasonically dispersing carbon nanotubes in N,N-dimethylformamide, the amount ratio of carbon nanotubes to N,N-dimethylformamide is 5-10g:100-150mL, and the size of the carbon nanotubes is 40-80nm in outer diameter, 10-15nm in inner diameter, and less than 10μm in length.
[0017] A method for preparing a wear-resistant plastic composition for a plastic stool comprises the following steps: PP particles, titanium dioxide-loaded fibers, polypropylene-g-maleic anhydride and zinc stearate are melt-extruded at 180-190°C in a twin-screw extruder, the extrudate is blended again with foamed TPU particles and a silicone oil defoamer, extruded at 190-200°C, cooled and dried at 70-80°C for 12-16 hours to obtain a wear-resistant plastic composition for plastic stools.
[0018] Beneficial effects of the present invention: (1) The wear-resistant plastic composition prepared by the present invention improves the wear resistance through carbon nanotubes, improves the anti-photooxidation performance of the wear-resistant plastic composition through the composite of nano-titanium dioxide and natural fibers, and promotes the composite of TPU, PP and natural fibers through a compatibilizer, thereby further improving the anti-photooxidation performance and mechanical properties of the wear-resistant plastic composition for plastic stools. The composition has a long service life outdoors under strong sunlight and has strong resistance to wind and sand weathering.
[0019] (2) The preparation method of the present invention uniformly compounds carbon nanotubes that are easy to agglomerate with TPU, and then wraps and fixes the carbon nanotubes with foamed TPU through a foaming treatment, thereby reducing the agglomeration of carbon nanotubes when the foamed TPU is blended with PP, thereby improving the wear resistance of the wear-resistant plastic composition. By loading nano-titanium dioxide on natural fibers and blending the natural fibers with PP, the incompatibility problem between nano-titanium dioxide and PP is solved, and the nano-titanium dioxide is uniformly dispersed in the wear-resistant plastic composition. The nano-titanium dioxide and the natural fibers work synergistically to improve the ultraviolet resistance of the wear-resistant plastic composition, thereby improving the anti-photooxidation performance of the wear-resistant plastic composition. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.
[0021] Example 1: A method for preparing a wear-resistant plastic composition for a plastic stool, comprising the following steps: S1. In a reactor, 10 g of dried TPU particles and 100 mL of N,N-dimethylformamide were magnetically stirred at 60°C for 1.5 h, 5 g of carbon nanotubes with an outer diameter of 40-80 nm, an inner diameter of 10-15 nm, and a length of less than 10 μm were ultrasonically dispersed in 100 mL of N,N-dimethylformamide to obtain a carbon nanotube dispersion, 100 mL of the carbon nanotube dispersion was added to the reactor, the temperature was raised to 60°C, and ultrasonic treatment was performed for 1 h. The solvent was then removed by rotary evaporation, and the precipitate was vacuum dried at 60°C for 40 h to obtain composite TPU particles.
[0022] S2. Put the composite TPU particles into an autoclave, introduce carbon dioxide to remove air, introduce carbon dioxide at a pressure of 15 MPa and 90° C. for 20 minutes, and then release the pressure to foam the composite TPU particles to obtain foamed TPU particles.
[0023] S3. After melting 20 g of o-methoxyphenol in a reactor, add 10 g of hemp fiber crushed through a 40-mesh sieve, add 5 mL of concentrated sulfuric acid to the reactor, heat to 160°C and stir to react for 60 min, cool, add 200 mL of acetone, stir to dissolve, and then slowly add 1.5 L of 2 M sulfuric acid solution, filter and separate the precipitate, wash the precipitate with deionized water and ether, and dry in vacuo at 80°C for 5 h to obtain the modified fiber.
[0024] S4. In a reactor, 10 g of the modified fiber was immersed in 100 mL of 0.1 M ammonium fluorotitanate solution, stirred for 10 h, filtered and collected the precipitate, and the precipitate was immersed in 150 mL of 0.3 M boric acid solution again, stirred for 3 h, filtered and collected the precipitate, and vacuum dried at 60 ° C for 5 h to obtain titanium dioxide loaded fiber.
[0025] S5. Melt-extrude 90 g of PP particles, 10 g of titanium dioxide-loaded fibers, 6 g of polypropylene-g-maleic anhydride and 1 g of zinc stearate at 180° C. in a twin-screw extruder, blend the extrudate with 30 g of foamed TPU particles and 1 g of a silicone oil defoamer again, extrude at 190° C., cool, and dry at 70° C. for 12 h to obtain a wear-resistant plastic composition for plastic stools.
[0026] Example 2: A method for preparing a wear-resistant plastic composition for a plastic stool, comprising the following steps: S1. In a reactor, 12.5 g of dried TPU particles and 125 mL of N,N-dimethylformamide were magnetically stirred at 65°C for 1.75 h, 7.5 g of carbon nanotubes with an outer diameter of 40-80 nm, an inner diameter of 10-15 nm, and a length of less than 10 μm were ultrasonically dispersed in 125 mL of N,N-dimethylformamide to obtain a carbon nanotube dispersion, 125 mL of the carbon nanotube dispersion was added to the reactor, the temperature was raised to 65°C, and ultrasonic treatment was performed for 1.25 h. The solvent was then removed by rotary evaporation, and the precipitate was vacuum dried at 65°C for 44 h to obtain composite TPU particles.
[0027] S2. Put the composite TPU particles into an autoclave, introduce carbon dioxide to remove air, introduce carbon dioxide at a pressure of 15.5 MPa and 95° C. for 30 minutes, and then release the pressure to foam the composite TPU particles to obtain foamed TPU particles.
[0028] S3. Melt 25 g of o-methoxyphenol in a reactor and add 12.5 g of jute fiber crushed through a 40-mesh sieve. Add 6 mL of concentrated sulfuric acid to the reactor, heat to 170°C and stir to react for 70 min. After cooling, add 225 mL of acetone, stir to dissolve, and then slowly add 1.65 L of 2 M sulfuric acid solution. Filter and separate the precipitate, wash the precipitate with deionized water and ether, and dry it in vacuo at 85°C for 5.5 h to obtain the modified fiber.
[0029] S4. In a reactor, 12.5 g of the modified fiber was immersed in 125 mL of 0.1 M ammonium fluorotitanate solution, stirred for 11 h, filtered and collected the precipitate, and the precipitate was immersed in 175 mL of 0.3 M boric acid solution again, stirred for 4 h, filtered and collected the precipitate, and vacuum dried at 65 ° C for 5.5 h to obtain titanium dioxide loaded fiber.
[0030] S5. Melt-extrude 95 g of PP particles, 12.5 g of titanium dioxide-loaded fibers, 7.5 g of polypropylene-g-maleic anhydride and 1.5 g of zinc stearate at 185 ° C in a twin-screw extruder, blend the extrudate with 35 g of foamed TPU particles and 1.5 g of silicone oil defoamer again, extrude at 195 ° C, cool and dry at 75 ° C for 14 h to obtain a wear-resistant plastic composition for plastic stools.
[0031] Example 3: A method for preparing a wear-resistant plastic composition for a plastic stool, comprising the following steps: S1. In a reactor, 15 g of dried TPU particles and 150 mL of N,N-dimethylformamide were magnetically stirred at 70°C for 2 h, 10 g of carbon nanotubes with an outer diameter of 40-80 nm, an inner diameter of 10-15 nm, and a length of less than 10 μm were ultrasonically dispersed in 150 mL of N,N-dimethylformamide to obtain a carbon nanotube dispersion, 150 mL of the carbon nanotube dispersion was added to the reactor, the temperature was raised to 70°C, and ultrasonic treatment was performed for 1.5 h. The solvent was then removed by rotary evaporation, and the precipitate was vacuum dried at 70°C for 48 h to obtain composite TPU particles.
[0032] S2. Place the composite TPU particles into an autoclave, introduce carbon dioxide to remove air, introduce carbon dioxide to saturate the autoclave at 16 MPa and 100° C. for 40 minutes, and then release the pressure to foam the composite TPU particles to obtain foamed TPU particles.
[0033] Carbon nanotubes are compounded with TPU particles through the physical adsorption capacity of carbon nanotubes. Under the assistance of ultrasound, carbon nanotubes are evenly adsorbed on the surface of TPU particles. Then, the TPU particles are micro-foamed through carbon dioxide high-pressure foaming technology, causing the TPU particles to foam and expand, coating the adsorbed carbon nanotubes, thereby evenly dispersing and fixing the carbon nanotubes in the foamed TPU particles. The uniform dispersion of carbon nanotubes greatly improves the wear resistance of the foamed TPU particles.
[0034] S3. Melt 30 g of o-methoxyphenol in a reactor and add 15 g of sisal fiber crushed through a 40-mesh sieve. Add 7 mL of concentrated sulfuric acid to the reactor, heat to 180°C and stir to react for 80 min. After cooling, add 250 mL of acetone, stir to dissolve, and then slowly add 1.8 L of 2 M sulfuric acid solution. After filtering and separating the precipitate, wash the precipitate with deionized water and ether, and dry it in vacuo at 90°C for 6 h to obtain the modified fiber.
[0035] The hydroxyl groups present in natural fibers are protonated in the acidic environment of concentrated sulfuric acid to form leaving groups, and are partially replaced by the catechol of o-methoxyphenol. The catechol is grafted into the natural fibers, and the nano-silica is loaded on the surface of the modified fibers by chemical grafting of the catechol functional groups with nano-silica, thereby improving the UV resistance of the modified fibers.
[0036] S4. In a reactor, 15 g of the modified fiber was immersed in 150 mL of 0.1 M ammonium fluorotitanate solution, stirred for 12 h, filtered and collected the precipitate, and the precipitate was immersed in 200 mL of 0.3 M boric acid solution again, stirred for 5 h, filtered and collected the precipitate, and vacuum dried at 70 ° C for 6 h to obtain titanium dioxide-loaded fiber.
[0037] Through the reducing ability of the catechol group on the surface of the modified fiber, under the promotion and reducing effect of boric acid, the nano-titanium dioxide is reduced and chemically bonded to the surface of the modified fiber, so that the surface of the modified fiber is evenly loaded with nano-titanium dioxide, thereby obtaining a titanium dioxide-loaded fiber with UV resistance.
[0038] S5. In a twin-screw extruder, 100 g of PP particles, 15 g of titanium dioxide-loaded fibers, 9 g of polypropylene-g-maleic anhydride and 2 g of zinc stearate were melt-extruded at 190°C, the extrudate was blended again with 40 g of foamed TPU particles and 2 g of silicone oil defoamer, extruded at 200°C, cooled and dried at 80°C for 16 h to obtain a wear-resistant plastic composition for plastic stools.
[0039] Titanium dioxide is easy to agglomerate and difficult to disperse in the PP matrix. After titanium dioxide is grafted and fixed on the surface of the modified fiber, the compatibility of the modified fiber and PP is improved by the compatibilizer polypropylene-g-maleic anhydride, thereby preventing the agglomeration of titanium dioxide in the PP matrix and improving the dispersion of titanium dioxide. The high strength of natural fibers can also improve the thermal stability and mechanical properties of PP, making the plastic composition have better stability under the weathering effect of strong natural wind and sand outdoors. In addition, the lignin contained in natural fibers is a natural antioxidant, which synergizes with the nano-titanium dioxide on the surface of natural fibers to improve the UV resistance of the plastic composition. Linear performance, the nano titanium dioxide loaded on the surface of the natural fiber increases the specific surface area and surface roughness of the titanium dioxide loaded fiber, increases the contact area between the natural fiber and the PP particles, enhances the bonding strength between the titanium dioxide loaded fiber and the PP matrix, and improves the wear resistance of the plastic composition; by blending with foamed TPU, not only TPU is introduced into the PP matrix, thereby improving the mechanical properties of the wear-resistant plastic composition, but also the agglomeration of carbon nanotubes is prevented, and the promoting effect of PP and TPU in the compatibilizer is utilized to uniformly disperse the wear-resistant filler carbon nanotubes in the wear-resistant plastic composition, thereby obtaining a wear-resistant plastic composition with good wear resistance.
[0040] Comparative Example 1: The difference from Example 1 is that in S5, composite TPU particles are used instead of foamed TPU particles to obtain a wear-resistant plastic composition for plastic stools.
[0041] Comparative Example 2: The difference from Example 1 is that in S4, natural fiber is used instead of modified fiber to obtain a wear-resistant plastic composition for plastic stools.
[0042] Comparative Example 3: The difference from Example 1 is that in S5, TPU particles are used instead of foamed TPU particles, and titanium dioxide-loaded fibers are not added to obtain a wear-resistant plastic composition for plastic stools.
[0043] The wear-resistant plastic compositions prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were injection molded and pressed into samples for performance testing. The samples were 30 mm diameter discs and 3 mm thick. Wear resistance tests were performed using a ball-on-disc tribometer under dry sliding conditions according to ASTM G99. The samples were weighed before and after the wear resistance test, and the wear rate was calculated. The wear-resistant plastic compositions prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were injection molded and pressed into samples for performance testing. The samples were 100 mm × 100 mm × 1 mm sheets. The tensile performance test was carried out on a mechanical testing machine according to GB / T1040-2006 at a tensile rate of 50 mm / min to test the tensile strength of the samples. In a xenon lamp test chamber, at a wavelength of 340 nm equipped with a daylight filter, the sample was subjected to a tensile test at a rate of 0.4 W / m 2 The light aging test was carried out at an irradiance of 100 nm / nm. The samples were illuminated continuously at 50°C for 200 h. The tensile strength was tested again after the samples were taken out. The results are shown in Table 1: Table 1 project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Wear rate (%) 0.283% 0.252% 0.216% 0.439% 0.304% 0.648% Tensile strength (Mpa) 28.34 28.57 29.12 27.61 27.85 25.73 Tensile strength after light aging (Mpa) 25.48 25.81 26.03 24.54 21.67 17.32 As can be seen from Table 1, the wear-resistant plastic composition prepared in the present invention has a low wear rate and a small degree of reduction in tensile strength after the light aging test, and can be well applied to plastic stool products in outdoor strong light environments.
[0044] In Comparative Example 1, since the composite TPU particles were not foamed, the carbon nanotubes on the surface of the composite TPU particles were easily detached during the melt blending process, and the dispersion was reduced, resulting in reduced friction resistance and tensile strength.
[0045] In Comparative Example 2, since the natural fiber is not modified, the degree of binding and uniformity of nano-titanium dioxide on the surface of the natural fiber are low, and it is easy to fall off during melt blending, resulting in reduced light oxidation resistance.
[0046] Comparative Example 3 is a control group, in which only TPU particles and PP particles are blended to prepare a wear-resistant plastic composition, which has low wear resistance and weak resistance to light aging. After the light test, the tensile strength decreases significantly.
[0047] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A wear-resistant plastic composition for plastic stools, characterized in that: Calculated by mass, it contains the following components: 90-100 parts of PP particles, 10-15 parts of titanium dioxide-loaded fibers, 6-9 parts of polypropylene-g-maleic anhydride, 1-2 parts of zinc stearate, 30-40 parts of foamed TPU particles, and 1-2 parts of silicone oil defoamer; The foamed TPU particles are prepared by the following steps: The composite TPU particles are placed in an autoclave, and after carbon dioxide is introduced to remove air, carbon dioxide is introduced at a pressure of 15-16 MPa and 90-100°C for 20-40 minutes to saturate the autoclave. The pressure is then released to foam the composite TPU particles to obtain foamed TPU particles. The titanium dioxide-loaded fiber is prepared by the following steps: The modified fiber is immersed in an ammonium fluorotitanate solution in a reactor and stirred for 10-12 hours. The precipitate is collected after filtration. The precipitate is immersed in a boric acid solution again and stirred for 3-5 hours. The precipitate is collected by filtration and vacuum dried to obtain titanium dioxide loaded fiber.
2. The wear-resistant plastic composition for plastic stools according to claim 1, characterized in that: The usage ratio of the modified fiber, ammonium fluorotitanate solution and boric acid solution is 10-15 g: 100-150 mL: 150-200 mL.
3. The wear-resistant plastic composition for plastic stools according to claim 2, characterized in that: The concentration of the ammonium fluorotitanate solution is 0.1M, and the concentration of the boric acid solution is 0.3M.
4. The wear-resistant plastic composition for plastic stools according to claim 2, characterized in that: The modified fiber is prepared by the following steps: After o-methoxyphenol is melted in a reactor, natural fibers crushed through a 40-mesh sieve are added thereto. Concentrated sulfuric acid is added to the reactor, the temperature is raised to 160-180° C., and the mixture is stirred and reacted for 60-80 minutes. After cooling, acetone is added thereto, and after stirring and dissolving, a 2M sulfuric acid solution is slowly added thereto. The precipitate is separated by filtration, washed, and vacuum dried to obtain the modified fiber.
5. The wear-resistant plastic composition for plastic stools according to claim 4, characterized in that: The dosage ratio of the o-methoxyphenol, natural fiber, concentrated sulfuric acid, acetone and sulfuric acid solution is 20-30 g: 10-15 g: 5-7 mL: 200-250 mL: 1.5-1.8 L.
6. The wear-resistant plastic composition for plastic stools according to claim 5, characterized in that: The natural fiber is one of hemp fiber, jute fiber, ramie fiber, kenaf and sisal fiber.
7. The wear-resistant plastic composition for plastic stools according to claim 1, characterized in that: The composite TPU particles are prepared by the following steps: In a reaction kettle, TPU particles and N,N-dimethylformamide are magnetically stirred at 60-70° C. for 1.5-2 hours, carbon nanotube dispersion is added to the reaction kettle, the temperature is raised to 60-70° C., ultrasonic treatment is performed for 1-1.5 hours, and then the solvent is removed by rotary evaporation. The precipitate is vacuum dried to obtain composite TPU particles.
8. The wear-resistant plastic composition for plastic stools according to claim 7, characterized in that: The usage ratio of the TPU particles, N,N-dimethylformamide and carbon nanotube dispersion is 10-15 g: 100-150 mL: 100-150 mL.
9. The wear-resistant plastic composition for plastic stools according to claim 8, characterized in that: The carbon nanotube dispersion is prepared by ultrasonically dispersing carbon nanotubes in N,N-dimethylformamide, and the usage ratio of the carbon nanotubes to the N,N-dimethylformamide is 5-10 g:100-150 mL.
10. The method for preparing a wear-resistant plastic composition for plastic stools according to claim 1, characterized in that: The preparation method comprises the following steps: PP particles, titanium dioxide-loaded fibers, polypropylene-g-maleic anhydride and zinc stearate are melt-extruded at 180-190°C in a twin-screw extruder, the extrudate is blended again with foamed TPU particles and a silicone oil defoamer, extruded at 190-200°C, cooled and dried at 70-80°C for 12-16 hours to obtain a wear-resistant plastic composition for plastic stools.
Citation Information
Patent Citations
Regenerated plastic particles and preparation method thereof
CN112143138A